Exhumation and anthropological study of the skeletal remains attributed to Liutprand, King of the Lombards (c. 690-744 AD) - Gaeta, Raffaele; Minozzi, Simona; Fornaciari, Antonio; Giuffra, Valentina; Riccomi, Giulia; Lubritto, Carmine; Fornaciari, Gino (Medicina Historica, 2020)
Liutprand, one of the greatest Lombard sovereigns, was born at the end of the 7th century AD and died in 744 AD. According to the Historia Langobardorum of Paolo Diacono, he was King of the Lombards from 712 to 744 AD. Over the centuries, his bones suffered from many episodes of translation and this is a crucial problem for the validation of the authenticity of the skeletal remains. Following a modern survey conducted at the end of the 19th century, the bones were arranged in a wooden box placed at the base of a pillar in the Cathedral of S. Pietro in Ciel d’Oro in Pavia. During the exhumation performed in January 2018 by the Division of Paleopathology of the University of Pisa the bones appeared extremely fragmented and in a poor state of preservation. Anthropological examination, imaging studies (CT and X-ray), 14C dating and stable isotopic analyses were performed. According to the anthropological examination, most of the remains belonged to a robust male with marked muscular insertions and an age at death between 40 and 50 years. The bones of two other individuals, an adult male with similar robusticity and dimensions and a young male, were also detected. A pathological tibia, exhibiting an enlarged diaphysis with a visible cloaca referable to a severe form of osteomyelitis, was associated with the younger male. 14C dating indicated that only one individual lived in the period consistent with that of Liutprand, while the other two were a few decades older than the Longobard king. Stable isotope values showed a rather good nutritional intake, with a varied diet of meat and fish for all the three individuals.